Chemsex and antiretroviral prescribing in an HIV cohort in Brighton, UK. Issue 7 (20th January 2022) - Adler, Zoe; Fitzpatrick, Colin; Broadwell, Nicholas; Churchill, Duncan; Richardson, Daniel
Abstract: Objectives: Chemsex has been reported among men who have sex with men (MSM) living with HIV. There have been concerns about potentially harmful drug–drug interactions between chemsex drugs and antiretroviral therapy (ritonavir and cobicistat). We aimed to describe the prevalence and patterns of chemsex users in our HIV clinic population and to evaluate antiretroviral prescribing among chemsex users. Methods: We undertook a cross‐sectional study of patients attending our HIV clinic between January 2019 and December 2020. We collected data on patients who disclosed recent recreational drug use including chemsex in the previous 3 months. Results: In all, 2202/2501 (88%) patients were asked about recreational drug use and 514 (23%) disclosed recreational drug use. Eighty‐two (4%) of these disclosed recent chemsex; 73 (89%) used crystal methamphetamine, 51 (62%) used gamma‐hydroxybutyrate (GHB)/gamma‐butyrolactone (GBL), 55 (67%) reported poly‐drug use and 63 (76%) reported injecting drug use. The chemsex users were all cis‐male MSM and were significantly older (53 vs. 46 years, p < 0.0001), and more likely to have had previous syphilis (73% vs. 28%, p < 0.0001) than patients reporting non‐chemsex drug use. All chemsex users were prescribed antiretrovirals and 74 (90%) had an undetectable HIV viral load; 31 (38%) patients were taking either ritonavir ( N = 12) or cobicistat ( N = 19) as part of their antiretroviral regimen and this was similar to other patients attending for HIV care [31/82 (38%) vs. 768/2419 (31%), p = 0.25]. Conclusions: The prevalence of chemsex users among our HIV clinic attendants is 4%, and 38% of these were prescribed either ritonavir or cobicistat. Chemsex use should be a factor in antiretroviral therapy decision‐making to avoid potential harm.